2011
DOI: 10.1007/s00464-011-2012-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of multiport versus laparoendoscopic single-site adrenalectomy for benign adrenal tumors

Abstract: The results demonstrate that LESS adrenalectomy is as safe and effective as conventional multiport laparoscopic adrenalectomy for benign adrenal tumors. In addition, LESS adrenalectomy provides short-term convalescence advantages over multiport laparoscopic adrenalectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…LESS-A was recently reported to be superior to CLA and so has become more common [4][5][6][7][8][9][10][11][12][13][14][15][16]. However, in spite of the technical difficulty of LESS-A, little is known BMI body mass index, VFA visceral fat area, TFA total fat area, ASA American Society of Anesthesiologists, APA aldosterone-producing adenoma, POD postoperative day about its learning curve and the factors associated with the outcomes of the procedure during the learning period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LESS-A was recently reported to be superior to CLA and so has become more common [4][5][6][7][8][9][10][11][12][13][14][15][16]. However, in spite of the technical difficulty of LESS-A, little is known BMI body mass index, VFA visceral fat area, TFA total fat area, ASA American Society of Anesthesiologists, APA aldosterone-producing adenoma, POD postoperative day about its learning curve and the factors associated with the outcomes of the procedure during the learning period.…”
Section: Discussionmentioning
confidence: 99%
“…Hirano et al [3], many studies have found that LESS-A has advantages over CLA [4][5][6][7][8][9][10][11][12][13][14][15][16]. At our institution, LESS-A was introduced in 2009.…”
mentioning
confidence: 92%
“…Without a functional single port or ergonomically feasible laparoscopic instruments for LESS, unsatisfactory pneumoperitoneal pressure or nonergonomic instruments will impair the procedural efficiency and possibly increase intraoperative complications. 11 Therefore, a comparative study to test existing single-access systems and instruments is essential before these expensive novel devices are widely adopted clinically.…”
Section: Discussionmentioning
confidence: 99%
“…According to our previous experience, the time required to set up a homemade single port is approximately 5e10 minutes. 9,11 To set up a homemade single port, several complicated steps such as surgical glove design/trimming, glove snapping, and trocar securing ligature are required, all of which are time-consuming (or time-limiting) procedures and require a certain amount of experience. If these steps are not carefully executed, gas leakage and port and trocar loosening may cause problems when performing LESS.…”
Section: Discussionmentioning
confidence: 99%
“…9 Several nonrandomized comparative series have been published in attempt to compare the outcomes of LESS-A with conventional LA in recent years; however, these results are inconsistent and, furthermore, their reported patient samples are still not large. 7,8,[10][11][12][13][14][15][16] Therefore, it is still unclear whether LESS-A is a truly less invasive and more feasible minimally invasive approach compared with conventional LA.…”
Section: Introductionmentioning
confidence: 99%